More jewelry making : techniques to take your projects to the next level - Michaels, Chris Franchetti (Teach yourself visually, 2012)
The visual way to advance your jewelry making Unlike other crafts that focus on a fairly narrow range of techniques and materials, jewelry making is very broad; the techniques encompass everything from bead stringing to metal stamping to working with different types of clay